Rootstock–scion exchanging mRNAs participate in the pathways of amino acid and fatty acid metabolism in cucumber under early chilling stress. Issue 1 (19th February 2022) - Liu, Wenqian; Wang, Qing; Zhang, Ruoyan; Liu, Mengshuang; Wang, Cuicui; Liu, Zixi; Xiang, Chenggang; Lu, Xiaohong; Zhang, Xiaojing; Li, Xiaojun; Wang, Tao; Gao, Lihong; et al.
Abstract: Cucumber ( Cucumis sativus L.) often experiences chilling stress that limits its growth and productivity. Grafting is widely used to improve abiotic stress resistance by exploiting a vigorous root system, suggesting there exists systemic signals communication between distant organs. mRNAs are reported to be evolving fortification strategies involving long-distance signaling when plants suffer from chilling stress. However, the potential function of mobile mRNAs in alleviating chilling stress in grafted cucumber is still unknown. Here, the physiological changes, mobile mRNA profiles, and transcriptomic and metabolomic changes in above- and underground tissues of all graft combinations of cucumber and pumpkin responding to chilling stress were established and analyzed comprehensively. The co-relationship between the cluster of chilling-induced pumpkin mobile mRNAs with differentially expressed genes and differentially intensive metabolites revealed that four key chilling-induced pumpkin mobile mRNAs were highly related to glycine, serine, and threonine synthesis and fatty acid β-oxidative degradation metabolism in cucumber tissues of heterografts. The verification of mobile mRNAs, potential transport of metabolites, and exogenous application of key metabolites of the glycerophospholipid metabolism pathway in cucumber seedlings confirmed the role of mobile mRNAs in regulating chilling responses in grafted cucumber. Our results build a link between the long-distance mRNAs of chilling-tolerant pumpkin and the fatty acid β-oxidative degradation metabolism of chilling-sensitive cucumber. They also help to uncover the mechanism of signaling interaction between scion and stock as a means of achieving chilling tolerance in grafted cucumber.